Synthesis of functionalized coumarins and quinolinones by NHC-catalyzed annulation of modified enals with heterocyclic C-H acids - Yetra, Santhivardhana Reddy; Roy, Tony; Bhunia, Anup; Porwal, Digvijay; Biju, Akkattu T. (Journal of Organic Chemistry, 2014)
N-Heterocyclic carbene (NHC) catalyzed lactonization and lactamization of 2-bromoenals with heterocyclic C–H acids proceeding via the α,β-unsaturated acyl azolium intermediates is reported. The reaction furnished coumarin- or quinolinone-fused lactone/lactam derivatives. In addition, results of the enantioselective version of this reaction using chiral NHC are presented.

Synthesis of 4H-chromenes by an unexpected, K3PO4-mediated intramolecular rauhut–currier type reaction - Bhunia, Anup; Yetra, Santhivardhana Reddy; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic & Biomolecular Chemistry, 2016)
In an attempt to develop the umpolung of Michael acceptors using chalcones having an enoate moiety under N-heterocyclic carbene (NHC) catalysis, a K3PO4-mediated intramolecular Rauhut–Currier type reaction was observed. This C(sp2)–C(sp2) coupling reaction afforded the biologically important 4H-chromenes in moderate to good yields. It is likely that the enol ether functionality acts as the nucleophilic trigger in this reaction.